Capitalizing on Desire: Reconfiguring 'the Social' and the Government of Poverty in the Philippines. Issue 6 (November 2015) - Seki, Koki
ABSTRACT: Tracing the contours of 'the social' is of critical importance today, since there is a widely shared understanding that 'the social' has been undergoing a fundamental mutation under the encroaching influence of globalization and neoliberalism. This mutation means that a population and its risks are increasingly administered and managed through the nurturing of free subjects, productive citizens and active communities. By focusing on conditional cash transfers as a poverty‐alleviation programme in the Philippines, this study examines how the contemporary government of poverty attempts to realize social inclusion through the nurturing of desires, habits and dispositions that are conducive to an 'investment in human capital'. The study argues that such regimes produce various forms of exclusion and counterclaims by the beneficiaries, and that these counterclaims, which reflect the popular notions of patronage and clientelism, have serious implications for envisioning the alternative configuration of 'the social'.